Dynamic power control scheme for C-V2X communication with channel inversion - Jieping ZHAI; Xiaolan LIU; Hailin XIAO (Dianxin kexue)
In cellular vehicle-to-everything（C-V2X）system, V2V（vehicle-to-vehicle）-based communication utilizes the spectrum resource of cellular users（CUE）to reduce the load of base stations, and thus realize partial near-field V2V communication.Although the V2V-based communication can improve the transmission rate of system, it causes co-frequency interference.To solve the problem, a dynamic power control scheme with channel inversion was proposed.In this scheme, channel inversion power control on V2V users（VUE）was performed to compensate the truncation interruption caused by limited transmission power in the non-truncated area, where the co-frequency interference between cellular users and V2V users was solved through dynamic power control.Furthermore, the optimal dual solution of objective function was obtained by Lagrange multiplier method and the optimal power allocation was carried out for cellular users and V2V users by bisection method, which met the rate requirements of all cellular users.Finally, the total transmission rate of V2V users was maximized.Numerical simulation results were shown that when the total outage probability of V2V users was 0.866, the proposed scheme was promoted by 48%.